2012
DOI: 10.1111/j.1438-8677.2012.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ‐specific responses of tomato growth and phenolic metabolism to nitrate limitation

Abstract: Phenolic compounds are secondary metabolites involved in plant innate chemical defence against pests and diseases. Their concentration varies depending on plant tissue and also on genetic and environmental factors, e.g. availability of nutrient resources. This study examines specific effects of low (LN) and high (HN) nitrogen supply on organ (root, stem and leaf) growth and accumulation of major phenolics [chlorogenic acid (CGA); rutin; kaempferol rutinoside (KR)] in nine hydroponically grown tomato cultivars.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 57 publications
6
43
0
Order By: Relevance
“…Nutritional treatment design was adapted from Han et al (2014); it was based on previous knowledge acquired on the tomato plant (see Le Bot et al 2009;Larbat et al 2012Larbat et al , 2014 and established from optimal conditions ensuring maximal growth of tomato plants in our lab conditions (see details in Han et al 2014). From DAS 8, a full nutrient solution adjusted to pH 5.5 was supplied daily to plants in a fully crossed design combining two nitrogen levels (optimal nitrogen [ON] vs. insufficient nitrogen [IN]) with two water levels (optimal water [OW] vs. drought [DT]).…”
Section: Plant Nutrition: Nitrogen and Water Inputsmentioning
confidence: 99%
“…Nutritional treatment design was adapted from Han et al (2014); it was based on previous knowledge acquired on the tomato plant (see Le Bot et al 2009;Larbat et al 2012Larbat et al , 2014 and established from optimal conditions ensuring maximal growth of tomato plants in our lab conditions (see details in Han et al 2014). From DAS 8, a full nutrient solution adjusted to pH 5.5 was supplied daily to plants in a fully crossed design combining two nitrogen levels (optimal nitrogen [ON] vs. insufficient nitrogen [IN]) with two water levels (optimal water [OW] vs. drought [DT]).…”
Section: Plant Nutrition: Nitrogen and Water Inputsmentioning
confidence: 99%
“…Other empirical formulae were assigned to cinnamic acid-like structures (CI1-3) by similarity with the CH backbone, although the presence of nitrogen suggested the presence of a primary amide derivative ( Table 2). Formation of amides with other amines, namely putrescine and spermidine, is well established in the literature for carboxylic acid metabolites in tomato extracts [16,17], thus explaining the hydrolysis of these secondary metabolites leading to the formation of CI1-3 ( Table 2). The semiquantitative distribution of CO and CI metabolites was not highly abundant, nor significantly different in root extracts derived from different bioeffector treatments and from control.…”
Section: Characterization and Semiquantitative Assessment Of Metabolitesmentioning
confidence: 84%
“…In particular, CY2 and H5 differentiate from control all roots treated with bioeffectors except B4 for the former and B1 for the latter, which strengthens the hypothesis that the inoculation of plant roots modifies their metabolism. This triggers a decreased response to stress that is ordinarily induced by either a phytopathogen attack or in the absence or scarcity of nutrients [17,18,[24][25][26][27][28]. Other variables in this axis may be seen as markers to differentiate B2 from control (U1 and U2) and from B1 (CY1, L11 and L13) (Fig.…”
Section: Pca Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…2). The mechanism behind this observation is not yet known, however, it has been reported that tomato varieties responded to varying levels of nitrogen nutrition by producing different levels of flavonoids and related phenolics (Larbat et al, 2012).…”
Section: Effects Of Differences In Tissue Nitrogen Levels On Susceptimentioning
confidence: 99%